Claiming spaces for urban art images in Beijing and Shanghai - Valjakka, Minna (Routledge handbook of graffiti and street art, 2016)
Since the mid-1990s, intricate and ever-changing negotiation processes are shaping the spaces - for urban art images in mainland China. The scenes and their
Gesehen am 15.09.2020